A decennial review of psychotraumatology: what did we learn and where are we going?. Issue 1 (31st December 2019) - Olff, Miranda; Amstadter, Ananda; Armour, Cherie; Birkeland, Marianne S.; Bui, Eric; Cloitre, Marylene; Ehlers, Anke; Ford, Julian D.; Greene, Talya; Hansen, Maj; Lanius, Ruth; Roberts, Neil; et al.
ABSTRACT: On 6 December 2019 we start the 10th year of the European Journal of Psychotraumatogy (EJPT), a full Open Access journal on psychotrauma. This editorial is part of a special issue celebrating the 10 years anniversary of the journal and acknowledging some of our most impactful articles of the past decade. In this editorial the editors present a decennial review of the field addressing a range of topics that are core to both the journal and to psychotraumatology as a discipline. These include neurobiological developments (genomics, neuroimaging and neuroendocrine research), forms of trauma exposure and impact across the lifespan, mass trauma and early interventions, work-related trauma, trauma in refugee populations, and the potential consequences of trauma such as PTSD or Complex PTSD, but also resilience. We address innovations in psychological, medication (enhanced) and technology-assisted treatments, mediators and moderators like social support and finally how new research methods help us to gain insights in symptom structures or to better predict symptom development or treatment success. We aimed to answer three questions 1. Where did we stand in 2010? 2. What did we learn in the past 10 years? 3. What are our knowledge gaps? We conclude with a number of recommendations concerning top priorities for the future direction of the field of psychotraumatology and correspondingly the journal. HIGHLIGHTS: Celebrating 10 years of the European Journal of Psychotraumatology the editors present a decennial review of core topics in the field and conclude with recommendations concerning top priorities for future research.